1988
DOI: 10.1073/pnas.85.16.5804
|View full text |Cite
|
Sign up to set email alerts
|

Alternative splicing generates messages encoding rat c-erbA proteins that do not bind thyroid hormone.

Abstract: The nucleotide and predicted amino acid sequences of two variant cDNAs [rat brain thyroid hormone receptor (rTRa) vI and vI], isolated from a rat brain cDNA library by using the Pst I fragment of v-erbA, showed virtual identity with the rat brain thyroid hormone receptor (rTRa)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
153
2
2

Year Published

1996
1996
2013
2013

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 274 publications
(159 citation statements)
references
References 22 publications
2
153
2
2
Order By: Relevance
“…The Thrb gene encodes three T 3 -binding TRb isoforms (b1, b2 and b3) whereas the Thra gene encodes one T 3 -binding TRa1 and two splicing variants (TRa2 and TRa3). These TRa variants have no T 3 -binding activity (Mitsuhashi et al 1988). We found that both isoforms Thra1 and Thrb1 were expressed in rat HG; Thra1 mRNA levels were higher than Thrb1 levels, given the much lower normalised Ct values (Fig.…”
Section: Thra and Thrb Expressionmentioning
confidence: 82%
“…The Thrb gene encodes three T 3 -binding TRb isoforms (b1, b2 and b3) whereas the Thra gene encodes one T 3 -binding TRa1 and two splicing variants (TRa2 and TRa3). These TRa variants have no T 3 -binding activity (Mitsuhashi et al 1988). We found that both isoforms Thra1 and Thrb1 were expressed in rat HG; Thra1 mRNA levels were higher than Thrb1 levels, given the much lower normalised Ct values (Fig.…”
Section: Thra and Thrb Expressionmentioning
confidence: 82%
“…In contrast, TRa is moderately expressed in several tissues. The a1 to a2 ratio is variable, being the most contrasted in the brain (Mitsuhashi et al, 1988). It has been suggested that the particular organization of the TRa locus contributes to the regulation of the a1/a2 balance.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the three transcripts (TR␣1, TR␤1, TR␤2) encoding isoforms that bind T3, we examined two closely related TR␣ splice variants collectively designated TR␣2. These variants give rise to isoforms that do not bind T3, but they are expressed at high levels in the developing brain (Lazar et al, 1988;Mitsuhashi et al, 1988a;Strait et al, 1990). As illustrated in Figure 6 A, TR␣1 mRNA and TR␤1 mRNA, but not TR␤2 or TR␣2 transcripts, were detected in microglia kept in vitro for up to 24 hr after purification from primary glial cultures.…”
Section: Expression Of Tr By Cultured Microglial Cellsmentioning
confidence: 99%